2022
DOI: 10.47280//revfacagron(luz).v38.n3.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity levels on antifungal activity of essential oil from Thymus against Fusarium oxysporum

Abstract: Thyme (Thymus sp.), a medicinal plant of the family Lamiaceae, is used in traditional medicine, contains a wide array of medicinally active components, in their great majority of a rather complex mixture of thymol, ρ-Cymene, γ-Terpinene, β-Caryophyllen, etc. This study aimed to evaluate the efficacy of Thymus vulgaris extract against Fusarium oxysporum f. sp.radicis-lycopersici strain under saline conditions, assuming soil with high salt content of the arid regions. Essential oil was extracted by hydrodistillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The present findings showed 45-80% enhancement in FOC biomass at 2-4 dS m −1 and 32-37% enhancement at 5-8 dS m −1 compared to the control. Boumaaza et al [31] indicated similar results in a way, as various levels of salinity (NaCl) enhanced the production of conidia in Fusarium oxysporum and exhibited a slight impact, at higher concentrations, on the germination of conidia. Tawfik et al [32] revealed that sodium salts at higher concentrations inhibit the growth of Fusarium semitectum.…”
Section: Discussionmentioning
confidence: 69%
“…The present findings showed 45-80% enhancement in FOC biomass at 2-4 dS m −1 and 32-37% enhancement at 5-8 dS m −1 compared to the control. Boumaaza et al [31] indicated similar results in a way, as various levels of salinity (NaCl) enhanced the production of conidia in Fusarium oxysporum and exhibited a slight impact, at higher concentrations, on the germination of conidia. Tawfik et al [32] revealed that sodium salts at higher concentrations inhibit the growth of Fusarium semitectum.…”
Section: Discussionmentioning
confidence: 69%